Review of Pronunciation fundamentals: Evidence-based perspectives for L2 teaching and research; Authors: Tracey M. Derwing and Murray J. Munro; Publisher: John Benjamins, 2015; ISBN: 9789027213273; Pages: 208 - Waniek-Klimczak, Ewa (Studies in Second Language Learning and Teaching, 2016)
Book Review